Nanoparticles: A Challenging Vehicle for Neural Stimulation - Colombo, Elisabetta; Feyen, Paul; Antognazza, Maria Rosa; Lanzani, Guglielmo; Benfenati, Fabio (Frontiers in Neuroscience, 2016)
Neurostimulation represents a powerful and well-established tool for the treatment of several diseases affecting the central nervous system. Although effective in reducing the symptoms or the progression of brain disorders, the poor accessibility of the deepest areas of the brain currently hampers the possibility of a more specific and controlled therapeutic stimulation, depending on invasive surgical approaches and long-term stability and biocompatibility issues. The massive research of the last decades on nanomaterials and nanoscale devices favored the development of new tools to address the limitations of the available neurostimulation approaches. This mini-review focuses on the employment of nanoparticles for the modulation of the electrophysiological activity of neuronal networks and the related transduction mechanisms underlying the nanostructure-neuron interfaces.